Fundamentals of legal method and rational legal action - Manrique Zegarra, César Edmundo (2021)
In support of this exhibition we welcome a set of criteria or beliefs that belong to a very old doctrine, practiced in all times and places, which might be called legal and political rationalism. Rationalism rationalist criteria that welcomes, supports as the belief in the equal capacity of human beings to make use of the legal right and distinguish right from wrong. Because legal reasoning on the belief that the (conventional) legal system is founded on the freedom of all human individuals to discuss, agree, agree and decide to act on the findings of the legal reason, in the process of creating the legal normative order. Political, because it assumes as true, which is a condition of legal action the responsibility that all people from the effects of their actions. The belief in equality (in the rational capacity) and freedom (of will) of the people is the basis for the attribution of responsibility (correlative to action) by the results of what was decided and done, being then necessary consequence rational legal legal action.